2018
DOI: 10.1177/2309499018777026
|View full text |Cite
|
Sign up to set email alerts
|

Familial patellar dislocation associated with t(15;20) (q24;q13.1)

Abstract: Patellar instability is a common debilitating injury affecting young active individuals. It accounts for approximately 3% of all knee injuries. We report a family, of which five members across three generations, who suffered from autosomal dominant familial recurrent patellar dislocation as well as short stature. All of them have recurrent patellar dislocations before the age of 15. The affected patients in all three generations have been genetically screened. Genotypical evaluation revealed a balanced translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…CM Jimmy Chan et al reported a familial recurrent patellar dislocation in 2018, which was considered autosomal dominant. Genotypic assessment suggested that the family pathogenesis was related to the balanced translocation of chromosomes 15 and 20 [ 16 ]. In this study, from the first generation to the third generation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CM Jimmy Chan et al reported a familial recurrent patellar dislocation in 2018, which was considered autosomal dominant. Genotypic assessment suggested that the family pathogenesis was related to the balanced translocation of chromosomes 15 and 20 [ 16 ]. In this study, from the first generation to the third generation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Can the results be applied to your patients/the population of interest? 12 10. Can the test be applied to your patient or population of interest?…”
Section: Table 9 Casp Diagnostic Study Checklistmentioning
confidence: 99%
“…Also, possible epidemiological factors and familial association have been suggested as risk factors for PD [4, 10–12, 28, 39, 50, 53].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, three other studies ind various numbers of participants with familial association with PD [12,23,59] Thompson et al suggest an inheritance of a recessive gene as a risk factor for PD [65], while others say that the cause of PD may be an autosomal dominant disorder [14,16,45,55]. Eleven studies show familial association with PD in a few members across generations [11,13,14,16,25,45,47,49,54,55,65] (Table 1 and Appendix 3).…”
Section: Familial Associationmentioning
confidence: 99%
“…Familial association has also been suggested as a risk factor for PD [5, 13, 14, 22, 41, 54], but the associations have not been well investigated [13, 14]. PD has been suggested as an autosomal dominant disease [16] as well as a clinical manifestation in rare syndromes, such as DiGeorge, Leri‐Weill, and Kabuki [35, 43, 50].…”
Section: Introductionmentioning
confidence: 99%